2004
DOI: 10.1210/jc.2003-031152
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine Dose for Remnant Ablation in Differentiated Thyroid Carcinoma: A Randomized Clinical Trial in 509 Patients

Abstract: Remnant ablation can be achieved by either administering an empiric fixed dose or using dosimetry-guided techniques. Because of the technical and logistic difficulties, most centers have adapted the fixed-dose or standard-dose technique for remnant ablation using (131)I. In the late 1970s, low-dose (131)I remnant ablation was introduced, and subsequently many centers confirmed the effectiveness of such therapy. However, the optimal dose (administered activity) of (131)I for remnant ablation is not yet settled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(68 citation statements)
references
References 40 publications
2
59
1
6
Order By: Relevance
“…While proponents of high RAI dose give more weightage to benefits of complete ablation rather than insignificant side effects of higher doses of RAI. A historical large clinical trial was conducted by Bal et al (2004) from India including 509 patients with WDTC who were divided into 8 treatment groups [received RAI from 15-50mCi (555-1850MBq)] to find out the optimal ablative dose. They concluded that a RAI of at least 25mCi (925MBq) had better chance of remnant ablation and any activity between 25-50mCi (925-1850MBq) of RAI was found adequate for remnant ablation (Bal et al, 2004).…”
Section: Low or High Dose Of Rai For Remnant Ablation?mentioning
confidence: 99%
See 1 more Smart Citation
“…While proponents of high RAI dose give more weightage to benefits of complete ablation rather than insignificant side effects of higher doses of RAI. A historical large clinical trial was conducted by Bal et al (2004) from India including 509 patients with WDTC who were divided into 8 treatment groups [received RAI from 15-50mCi (555-1850MBq)] to find out the optimal ablative dose. They concluded that a RAI of at least 25mCi (925MBq) had better chance of remnant ablation and any activity between 25-50mCi (925-1850MBq) of RAI was found adequate for remnant ablation (Bal et al, 2004).…”
Section: Low or High Dose Of Rai For Remnant Ablation?mentioning
confidence: 99%
“…A historical large clinical trial was conducted by Bal et al (2004) from India including 509 patients with WDTC who were divided into 8 treatment groups [received RAI from 15-50mCi (555-1850MBq)] to find out the optimal ablative dose. They concluded that a RAI of at least 25mCi (925MBq) had better chance of remnant ablation and any activity between 25-50mCi (925-1850MBq) of RAI was found adequate for remnant ablation (Bal et al, 2004). However, this study was criticized due to inadequate surgery in 28% patients resulting in higher neck uptake of RAI, variable time between ablation and surgery and low number of patients in groups who received least RAI.…”
Section: Low or High Dose Of Rai For Remnant Ablation?mentioning
confidence: 99%
“…Nevertheless, it is possible to have some idea when observing therapeutic efficiency in patients without renal dysfunction. In literature, activities as low as 1.8 GBq (50 mCi) or 1.1 GBq (30 mCi) have failed in therapy in about 40% to 50% of the cases (16)(17)(18), when prior dosimetric studies were unavailable. Thus, the administration of similar activities to patients should be avoided, except in specific and documented cases, or when dosimetric studies have preceded therapy.…”
Section: Case Reportmentioning
confidence: 99%
“…The gold standard of scientific evidence of course traditionally consists of randomized controlled trial results and, ideally, of confirmatory data from subsequent such trials in different populations. In DTC management, however, this type of published data is lacking, except regarding 131 I activities for radioiodine thyroid remnant ablation (RRA) [6,7] and regarding RRA stimulation with recombinant human thyroid-stimulating hormone (rhTSH) versus with thyroid hormone withdrawal [8][9][10][11]. Only recommendations that can be backed up by results conforming to this gold standard should be graded "A" or "F" (Table 1) in the ATA guidelines; it appears to be an over-interpretation to rate the strength of evidence of other kinds of published studies according to "outcome".…”
Section: Introductionmentioning
confidence: 99%